Postexposure Protective Efficacy of T-705 (Favipiravir) Against Sudan Virus Infection in Guinea Pigs. (2nd July 2018) - Rahim, Md N; Zhang, Zirui; He, Shihua; Zhu, Wenjun; Banadyga, Logan; Safronetz, David; Qiu, Xiangguo
Abstract: Filoviruses such as Ebola virus (EBOV), Marburg virus (MARV), and Sudan virus (SUDV) cause deadly viral hemorrhagic fever in humans, with high case-fatality rates; however, no licensed therapeutic agent or vaccine has been clinically approved to treat or prevent infection. T-705 (favipiravir) is a novel antiviral drug that has been approved for the treatment of influenza in Japan. T-705 exhibits broad-spectrum antiviral activity against different viruses, including MARV and EBOV, and here, we are the first to report the in vitro and in vivo antiviral activity of T-705 against SUDV. T-705 treatment reduced SUDV replication in Vero E6 cells. Subcutaneous administration of T-705, beginning 1–4 days after infection and continuing for 7 days, significantly protected SUDV-infected guinea pigs, with a survival rate of 83%–100%. Viral RNA replication and infectious virus production were also significantly reduced in the blood, spleen, liver, lungs, and kidney. Moreover, early administration of low-dose T-705 and late administration (at 5 days after infection) of higher-dose T-705 also showed partial protection. Overall, our study is the first to demonstrate the antiviral activity of T-705 against SUDV, suggesting that T-705 may be a potential drug candidate for use during outbreaks.